Perceptions of adults on the use of tobacco and alcoholic beverages - Daranciang, Cecilia B. 1928-
Advancement of medical science has brought about countless inventions. Since the turn of the century, there has been hundreds of important drugs developed. This study was conducted to determine the perceptions of adults regarding the use of tobacco and alcohol in Mangatarem, Pangasinan. The descriptive method of research with the use of an interview was employed in this study. The findings of the study showed that majority of the respondents perceive both tobacco and alcohol as medicines and are unaware of the harmful effects of such drugs. The study concluded that there is a need for drug education with emphasis on tobacco and alcohol for all levels and a need for re-direction of values not only for adults but also for the young.